Identification of critical success factors for sustainable development of biofuel industry in China based on grey decision-making trial and evaluation laboratory (DEMATEL). (10th September 2016) - Liang, Hanwei; Ren, Jingzheng; Gao, Zhiqiu; Gao, Suzhao; Luo, Xiao; Dong, Liang; Scipioni, Antonio
Abstract: Biofuel as a promising pathway for substituting the traditional fossil fuels, mitigating environmental contaminations, and enhancing the energy security has attracted more and more attention in China. This study aims at identifying the critical success factors for promoting the sustainable development of biofuel industry and helping the stakeholders/decision-makers to draft the appropriate strategic measures for enhancing the sustainability of biofuel industry in China. A generic methodology in which the decision-makers are allowed to use linguistic terms to express their views and options, multiple decision-makers are allowed to participate in the decision-making, has been developed to prioritize the factors influencing the sustainability of biofuel industry and to identify the cause–effect relationships among these factors. The three factors, including government support degree, competitiveness, and local acceptability are identified as the most critical factors for promoting the sustainable development of biofuel industry in China, but they are all effects rather than the origins of the problems existed in the biofuel industry of China. In contrast, maturity, safety and reliability, complexity, conversion efficiency, and investment cost are the most important causes, and they are also the origins of the problems existed in the biofuel industry of China. Six effective strategic measures including popularizing the use of biofuels in large scales, subsidies and tax exemption policies, investing more on R&D on biofuel technologies, encouraging more private enterprises and joint ventures to participate in the biofuel industry, developing the integrated utilization manner of biofuels by further developing the byproducts of biofuels, and popularizing the use of biodiesel and bioethanol among the vehicle users through publicity and education have been proposed for promoting the sustainable development of China's biofuel industry according to the obtained results.